Adrenalectomy for Secondary Malignancy: Patients, Outcomes, and Indications. Issue 6 (December 2021) - Wachtel, Heather; Roses, Robert E.; Kuo, Lindsay E.; Lindeman, Brenessa M.; Nehs, Matthew A.; Tavakkoli, Ali; Parangi, Sareh; Hodin, Richard A.; Fraker, Douglas L.; James, Benjamin C.; Carr, Azadeh A.; Wang, Tracy S.; et al.
Abstract : Objective: The goal of this study was to examine a multi-institutional experience with adrenal metastases to describe survival outcomes and identify subpopulations who benefit from adrenal metastasectomy. Background: Adrenalectomy for metastatic disease is well-described, although indications and outcomes are incompletely defined. Methods: A retrospective cohort study was performed of patients undergoing adrenalectomy for secondary malignancy (2002–2015) at 6 institutions. The primary outcomes were disease free survival (DFS) and overall survival (OS). Analysis methods included Kaplan-Meier and Cox proportional hazards. Results: Of 269 patients, mean age was 60.1 years; 50% were male. The most common primary malignancies were lung (n = 125, 47%), renal cell (n = 38, 14%), melanoma (n = 33, 12%), sarcoma (n = 18, 7%), and colorectal (n = 12, 5%). The median time to detection of adrenal metastasis after initial diagnosis of the primary tumor was 17 months (interquartile range: 6–41). Post-adrenalectomy, the median DFS was 18 months (1-year DFS: 54%, 5-year DFS: 31%). On multivariable analysis, lung primary was associated with longer DFS [hazard ratio (HR): 0.49, P = 0.008). Extra-adrenal oligometastatic disease at initial presentation (HR: 1.84, P = 0.016), larger tumor size (HR: 1.07, P = 0.013), chemotherapy as treatment of the primary tumor (HR: 2.07 P = 0.027) and adjuvant chemotherapy (HR: 1.95, P = 0.009) were associated with shorter DFS. Median OS was 53 months (1-year OS: 83%, 5-year OS: 43%). On multivariable analysis, extra-adrenal oligometastatic disease at adrenalectomy (HR: 1.74, P = 0.031), and incomplete resection of adrenal metastasis (R1 margins; HR: 1.62, P = 0.034; R2 margins; HR: 5.45, P = 0.002) were associated with shorter OS. Conclusions: Durable survival is observed in patients undergoing adrenal metastasectomy and should be considered for subjects with isolated adrenal metastases.